Biomimetic remineralization of artificial caries dentin lesion using Ca/P-PILP. Issue 11 (November 2020) - Chen, Ruitian; Jin, Runze; Li, Xin; Fang, Xiaolin; Yuan, Ding; Chen, Zhuo; Yao, Shasha; Tang, Ruikang; Chen, Zhi
Highlights: Ca/P-PILP was synthesized at high Ca2+ concentration without precipitation. Electron Probe Micro Analyzer was used to investigate element contents. Artificial caries dentin lesion could be biomimetic remineralized by Ca/P-PILP. Remineralization could improve the bond strength of artificial caries dentin lesion. Abstract: Objective: To assess the ultrastructural change of demineralized dentin collagen during calcium phosphate polymer-induced liquid precursor (Ca/P-PILP) mediated remineralization process and to evaluate the biomimetic remineralization potential of high concentration Ca/P-PILP at demineralized artificial caries dentin lesion, additionally to investigate the bond interfacial integrity as well as the bonding strength of the biomimetic remineralized artificial caries dentin lesion. Methods: Demineralized dentin collagen of 5 μm thick was biomimetically remineralized with low, medium concentration Ca/P-PILP for 10 days and high concentration Ca/P-PILP for 10, 15, 20 days. Artificial caries dentin lesion at a thickness of 150 ± 50 μm was biomimetically remineralized with high concentration Ca/P-PILP for 20 days. The biomimetic remineralization of demineralized dentin collagen was observed by scanning electron microscopy (SEM). The biomimetic remineralization intensity and depth of artificial caries dentin lesion was assessed by Electron Probe Micro Analyzer (EPMA). The bonding interfacial integrity between remineralized artificial caries dentin and composite resin was observed by Swept-source optical coherence tomography (SS-OCT) and the bonding strength of remineralized artificial caries dentin was evaluated by micro-tensile bond strength analysis (μTBS). Results: Solely PAA-PASP solution and solely saturated Ca/P solution can't achieve dentin collagen remineralization. Increased concentration of Ca/P-PILP and prolonged remineralization time can enhance the biomimetic remineralization intensity of demineralized dentin collagen. After treating with high concentration Ca/P-PILP, a 150 ± 50 μm thick layer of demineralized artificial caries dentin lesion was not fully remineralized, and the biomimetic remineralization intensity reached up to 88.0%. Furthermore, a better bonding interfacial integrity with less microgap and increased bond strength at both baseline level and aging level were observed when artificial caries dentin lesion was biomimetically remineralized with high concentration Ca/P-PILP. Significance: Biomimetic remineralization of demineralized caries dentin lesion promotes its clinical properties for resin composited adhesive restoration.